PERTUMBUHAN POPULASI Spirulina platensis DALAM MEDIA LIMBAH CAIR BAHAN OLAHAN KECAP DAN MEDIA ZARROUK - Junedi Tinambunan; Marini Wijayanti; Dade Jubaedah (Jurnal Akuakultur Rawa Indonesia, 2017)
ABSTRACTThe aims of this research were to study the influence of mixed industrial soy sauce liquid waste and Zarrouk medium mixture on population density and specific growth rate of Spirulina platensis on a short periode. This study has been conducted from March to April 2017 in the Laboratory of Aquaculture, Aquaculture study Program, Faculty of Agriculture, University of Sriwijaya. This research was arranged according to completely randomized design (CRD) with 5 treatment levels and 3 replications. The treatment levels consisted of P1 (0 % industrial soy sauce liquid waste + 100 % Zarrouk medium), P2 (25 % industrial soy sauce liquid waste + 75 % Zarrouk medium), P3 (50 % industrial soy sauce liquid waste + 50 % Zarrouk medium), P4 (75 % industrial soy sauce liquid waste + 25 % Zarrouk medium), P5 (100 % industrial soy sauce liquid waste + 0 % Zarrouk medium). The parameters observed during the study were population density and the maximum specific growth rate. The result of this study showed that the treatment P2 gave the best in maximum density (60.6 g.L-1 ) and specific growth rate (14.66%. day-1). Keywords: Spirulina platensis, the liquid waste ketchup, Zarrouk media.